Overview of Gadget Utilization and Its Effect on Growth and Development in Preschool Children - Rini Andriani (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
The gadget utilization among preschoolers in connection with technological advances is known to have positive and negative effects on growth and development. This study aims to identify the overview of gadget utilization and its effect on growth and development in preschool children. An analytic survey with a cross-sectional design was conducted by filling out questionnaires carried out by parents. The anthropometric measurements and developmental assessments were carried out using Indonesia Developmental Pre-screening Questionnaire (IDPQ). A hundred children and their parents participated in this study. It was found that 82% of parents lent their gadgets, and 89% taught their children to use gadgets. There were similarities in gadget utilization between parents and children, namely watching videos (73% and 90%) and communicating (92% and 40.4%). The duration of the gadget utilization by children was high, 3.7±2.2 hours/day. However, no significant correlation in the analysis between the duration of smartphone usage and nutritional status (p: 0.599). In children with different IDPQ values, there was no significant difference in the duration of device usage (p: 0.991). It can concluded the duration of the gadget utilization in children carried out by their parents did not affect the growth and development of the children.